Crystal structure of (E)-N′-(2-chloro-6-hydroxybenzylidene)-2-hydroxybenzohydrazide, C14H11ClN2O3 - Liu Jianlian; Hao Hong; Du Chaojun (Zeitschrift für Kristallographie - New Crystal Structures)
C14H11ClN2O3, monoclinic, P21/n (no. 14), a = 7.0242(11) Å, b = 25.375(4) Å, c = 7.6789(13) Å, β = 111.2752°, V = 1275.4(4) Å3, Z = 4, R gt(F) = 0.0349, wR ref(F 2) = 0.1123, T = 296(2) K.